2017
DOI: 10.1136/postgradmedj-2016-134513
|View full text |Cite
|
Sign up to set email alerts
|

Reducing unnecessary testing: an intervention to improve resident ordering practices

Abstract: Education in the form of cost reminders did not significantly reduce the overall ordering of the most common daily laboratory testing in our academic teaching service. We believe further research is needed to fully evaluate the effectiveness of other education forms on the redundant ordering of tests in the hospital setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 18 publications
1
16
0
Order By: Relevance
“…Melendez-Rosado et al 16 demonstrated that a programme of education had no significant impact on the ordering behaviour of medical residents. However, Miyakas et al 12 were able to demonstrate a decrease in the number of inappropriate tests ordered by trainee doctors after an educational session, although the effect was short-lived and only lasted one semester 12.…”
Section: Discussionmentioning
confidence: 99%
“…Melendez-Rosado et al 16 demonstrated that a programme of education had no significant impact on the ordering behaviour of medical residents. However, Miyakas et al 12 were able to demonstrate a decrease in the number of inappropriate tests ordered by trainee doctors after an educational session, although the effect was short-lived and only lasted one semester 12.…”
Section: Discussionmentioning
confidence: 99%
“…Many interventions are multifaceted incorporating both a component of person‐oriented intervention as well as change in system design or process. Table lists the studies reviewed that have used education and reminders, audit and feedback, computer physician entry order systems, and forcing restraints …”
Section: Improving Test Utilizationmentioning
confidence: 99%
“…Melendez et al's study focussed around a 30‐minute teaching session for residents, followed by visual reminders of the cost of laboratory tests that were placed at computer stations. After 3 months of intervention, they found slight decrease in number of combined CBC and differentials ordered (the costlier combination) but noted an increase in total CBCs requested.…”
Section: Educational Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Implementing a variety of quality improvement projects and measures to increase the awareness about the AUC and facilitate its use can serve this purpose. Reminders to providers in the electronic medical record, smartphone applications and pocket cards can be employed to be effective tools in changing the culture of ordering unnecessary tests 46. Some institutions have a designated area near the providers’ desks or work stations where posters and flow charts are readily available to serve as a reminder for the quality improvement intervention.…”
Section: The Impact Of the Upcoming Reimbursement Changesmentioning
confidence: 99%